Effective adsorption and photodegradation of methyl orange by TiO2-chitosan supported glass plate photocatalysis. (21st March 2017) - Amir, Muhammad Nur Iman; Muhd Julkapli, Nurhidayatullaili; Hamid, Sharifah Bee Abd
Abstract : In this study, Chitosan (Cs) biopolymer was incorporated into TiO2 nanoparticles as a support and adsorption site, forming an effective photocatalyst system. The stability and separation ability of the Cs–TiO2 photocatalyst system improved as it is further immobilised onto the surface of the glass plate. The surface interactions and the band gap of Cs–TiO2(DP25) /glass photocatalyst have been determined using techniques including FESEM + EDS, FTIR and UV-DR analysis. The photocatalytic activity has been demonstrated on the simulated methyl orange (MO) solution (10 ppm) irradiated under ultraviolet light (6 W, λ = 312 and 365 nm) with different photodegradation parameters such as number of layers, concentration and pH of MO solution. It indicated that Cs–TiO2(DP25) /glass photocatalyst exhibited excellent formation of coordinate covalent bonding between Ti-O to Si-O, Ti-O-to-NH2 or Ti-O-to-OH groups. The optimum photodegradation recorded for the Cs–TiO2(DP25) /glass photocatalyst has reached to 78%, with 10 ppm of MO concentration, at a normal pH and 1 h retention time. Meanwhile, optimum adsorption process has been recorded to be more than 70%. It was concluded that the combination of the adsorption and photodegradation process from Cs–TiO2(DP25) /glass photocatalyst has great potential for treating wastewater for other types of organic/inorganic pollutants.